Influencia del absentismo laboral en el cumplimiento de funciones y rendimiento de los colaboradores de la empresa Export Valle Verde S.A.C. Trujillo. 2022 - Paz Hernández, Luz Verónica (2023)
The present investigation was carried out with the aim of analyzing how labor absenteeism intervenes in the performance and fulfillment of functions of the workers of the agro-exporting company Export Valle Verde S.A.C - Trujillo. The study population consisted of 512 collaborators, the sampling was probabilistic, the sample with which it was worked was 220 workers registered in the company’s payroll; the instruments used were a questionnaire applied on the sample, and an interview applied to personnel in the area of human resources, in order to be able to carry out the collection of information regarding the variables of absenteeism, productive performance and performance of duties; basic research and had a non-experimental - transversal design. The results show that workers often perceive unjustified absenteeism, in turn most workers have characteristics that imply greater probability of work absenteeism. It is concluded that unjustified absenteeism without prior notice is the most frequent, which negatively impacts the productivity and quality of the work of the employees, generating an unstable environment, stressful and unhealthy relationships between workers.